2019
DOI: 10.1002/bies.201800221
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Interference, Crossover Maturation, and Human Aneuploidy

Abstract: A striking feature of human female sexual reproduction is the high level of gametes that exhibit an aberrant number of chromosomes (aneuploidy). A high baseline observed in women of prime reproductive age is followed by a dramatic increase in older women. Proper chromosome segregation requires one or more DNA crossovers (COs) between homologous maternal and paternal chromosomes, in combination with cohesion between sister chromatid arms. In human females, CO designations occur normally, according to the dictat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 87 publications
(321 reference statements)
2
36
0
Order By: Relevance
“…This evidence comes from a variety of organisms such as tomatoes, mice and humans and lead to the hypothesis that DNA loops along SCs are regularly spaced, with the consequence that the degree of chromatin compaction is reflected in the length of the SC, as smaller loops would yield longer SCs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Conversely, the same amount of linear DNA organized in longer loops would result in shorter chromosomal axes [ 11 , 32 ]. In the chicken and most avian karyotypes, heterochromatin is mainly confined to microchromosomes [ 33 ], thus the lower DNA density found here in microbivalents seems to contradict the general view over the DNA arrangement in heterochromatin vs. euchromatin along meiotic axes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence comes from a variety of organisms such as tomatoes, mice and humans and lead to the hypothesis that DNA loops along SCs are regularly spaced, with the consequence that the degree of chromatin compaction is reflected in the length of the SC, as smaller loops would yield longer SCs [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Conversely, the same amount of linear DNA organized in longer loops would result in shorter chromosomal axes [ 11 , 32 ]. In the chicken and most avian karyotypes, heterochromatin is mainly confined to microchromosomes [ 33 ], thus the lower DNA density found here in microbivalents seems to contradict the general view over the DNA arrangement in heterochromatin vs. euchromatin along meiotic axes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, for a given genome size, chromosomes with longer loops have shorter axes while chromosomes with shorter loops have longer axes [ 6 , 10 ]. Considering the role of axis length in determining the frequency of CO events, longer/shorter loops imply shorter/longer axes, which in turn imply fewer/more COs [ 11 ]. A great deal of this argument is based on estimates of DNA loop length in micrographs of pachytene nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Also, acrocentric macrobivalents have similar COs frequencies at centromeric and telomeric regions of the long arm (Fig 6). The organization of the DNA loops along meiotic axes is known to influence the number of recombination interactions that are solved as CO events [59]. In fact, birds have higher ratio of SC length per DNA amount than mammals and reptiles, and also have higher recombination rates, supporting the argument that DNA organization along the SC influences CO rates [60].…”
Section: Localized and Non-localized Crossover Distributions Coexist mentioning
confidence: 94%
“…Recent studies have also suggested roles for Mlh1–Mlh3 in chromosome disjunction and crossover interference (Chakraborty et al, 2017; ClaeysBouuaert & Keeney, 2017). Crossover interference, seen in many organisms such humans, mice, Drosophila and Caenorhabditis elegans , regulates the spatial distribution of crossovers; the formation of a crossover lowers the probability of a second crossover nearby (Wang et al, 2019). Widely spaced crossovers, exhibiting interference, help to ensure the fidelity of chromosome segregation.…”
Section: Baker's Yeast Mutl Homolog Proteinsmentioning
confidence: 99%